Respiratory Syncytial Virus and Parainfluenza Virus: Characterizing Distinct Clinical Profiles and How They Shift with Bacterial Coinfection - Nie, Bo; Cheng, Ying; Hu, Hong-bo (Journal of Pediatric Infectious Diseases, 2023)
Objective The objectives are to characterize the distinct clinical profiles of respiratory syncytial virus (RSV) and parainfluenza virus (PIV) infections and how these profiles shift with the addition of bacterial coinfections.Methods This retrospective study analyzed data from more than 1,000 hospitalized children to compare RSV monoinfection with PIV monoinfection, as well as RSV/PIV coinfection with bacteria with monoinfection.Results Significant differences in age distribution (p < 0.001), clinical presentation (p < 0.001), the proportion of pneumonia (p < 0.001), mechanical ventilation (p = 0.004), pediatric intensive care unit (PICU) admission (p = 0.001), and duration of hospitalization (p = 0.003) were observed between RSV and PIV monoinfections. Children with bacterial coinfections had a higher proportion of cough (p = 0.004), wheezing (p = 0.003), rales (p = 0.002), pneumonia (p = 0.002), and PICU admission (p = 0.021) than PIV monoinfection. Notably, the duration of hospitalization for children with bacterial coinfections was longer than that of those infected with a single PIV infection, with a statistically significant difference (p = 0.028).Conclusion Compared with PIV, RSV was more likely to cause severe respiratory tract infections. Coinfection of PIV with bacteria may have exacerbated the severity of acute respiratory tract infections and worsened the symptoms.
Keywords: acute respiratory tract infections; respiratory syncytial virus; parainfluenza virus; coinfections